The process of creating algorithms for fundamental taekwondo training in the WTF style - Semenova, G. I.; Erkomayshvili, I. V.; Erkomayshvili, I. V.; Ryabov, G. A.; Pshenitsyn, K. K. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to determine the perspective of instructors regarding the implementation of algorithms in the teaching of fundamental techniques in Taekwondo.